Study on the Development Height of Overburden Water-Flowing Fracture Zone of the Working Face. (18th March 2021) - Ding, Ke; Wang, Lianguo; Wang, Wenmiao; Wang, Kai; Ren, Bo; Jiang, Chongyang
Abstract : Mining-induced fractures in underground coal mining face affect the stability of overburdens and provide preferential channels for water and material transfer in the underground environment. Therefore, to study the development of water-flowing fracture zones in overburdens of working face and goaf is of great significance for roof control, gas drainage, water resistance, disaster reduction, and efficient mining from the mining. In this study, a new method for predicting the development of overburden water-flowing fracture zone height (DHOWFFZ) was proposed based on the characteristics of overburden rock in No. 3 coal seam of Xin'an Coal Mine. First, the stope of No. 3 coal seam exhibits a rock stratum structure of mudstone and sandstone overlapping. Considering this characteristic, the overburden strata of No. 3 coal seam are divided into several "mudstone-sandstone" rock stratum groups. Furthermore, the ultimate tensile deformation of soft rock is greater than that of hard rock. It is proposed to judge the development degree of penetrating fracture in each rock stratum by adopting the elongation rate of mudstone intermediate layer. Meanwhile, the DHOWFFZ of "mudstone sandstone" composite rock stratum structure in the 3402 working face of No. 3 coal seam is calculated to be smaller than 43.1 m according to the actual situation. Finally, the DHOWFFZ in the 3402 working face was measured in the field, which verifies the rationality of the new DHOWFFZ prediction method. The research results provide new ideas for the prediction of DHOWFFZ and are helpful for future research in related fields.